Berberine Supplement and Resistance Training May Ameliorate Diazinon Induced Neural Toxicity in Rat Hippocampus Via the Activation of the TrkB and ERK Signaling Pathway - Shakouri, Elham; Azarbayjani, Mohammad Ali; Jameie, Seyed Behnamedin; Peeri, Maghsoud; Farhadi, Mona (International Clinical Neuroscience Journal, 2020)
Background: Diazinon is an organophosphate pesticide that is broadly applied to control insects which causes oxidative damages in hippocampus tissue. We aimed to examine whether resistance training and berberine supplementation can protect the hippocampus against berberine-induced neural toxicity. Methods: Fifty-six male Wistar rats were assigned randomly into eight groups of seven including: Control (Ctrl), Sham (normal saline), T1 (diazinon + berberine chloride (2 mg/kg) + resistance training), T2 (diazinon + berberine chloride [15 mg/kg] + resistance training), T3 (diazinon), T4 (diazinon +resistance training), T5 (diazinon + berberine chloride [2 mg/kg]), and T6 (diazinon + berberine chloride [15 mg/kg]). In the experimental groups, diazinon was intraperitoneally administered at a dose of 1.5 mg/kg. In the training groups, rats were trained every three days for six weeks and 8-12 dynamic movements (repetitions) during each climb (six climbs for two sets). The expression of hippocampus PI3K and CDK genes and TrkB and ERK protein levels were evaluated in the brain of diazinon-treated rats. Results: The protein expression of ERK and TrkB were increased following the treatment of diazinonintoxicated rats with berberine and resistance training (P=0.001). The administration of berberine at a dose of 15 mg/kg in combination with resistance training significantly (P=0.001) decreased the cell death rate in the hippocampus. Diazinon treatment caused extensive apoptosis in the hippocampus region of the rats’ brain (P=0.001). The gene expression of PI3K and CDK was significantly increased and the cell death rate significantly decreased (P=0.001) in the hippocampus following the treatment of rats with berberine and resistance training. Conclusion: Six weeks of resistance training in combination with berberine treatment significantly reduced apoptosis in the hippocampus region of diazinon-intoxicated rats. It seems the neuroprotection effects of berberine and resistance training are mediated by the stimulation of the expression of enzymes responsible for the antioxidant defense within neuronal cells